PERJALANAN PANJANG FOTOGRAFI SEBELUM ABAD-21 - Anin Astiti (Pendhapa, 2011)
To track back the History of Photography is like unraveling a messy ball ofyarn. Photography is considered a new form of art. lts origin started on 17thcentury as discovered by a Fine Artist and then followed along the way byscientists, philosophers and otherartists from different branches of arts. Theearly stage of photography focused more on the technique of developing,from the invention of plates and the negative-positive process. Thedevelopment of camera instruments such as the invention of lenses, shuttersand others went simultanously along the way.Keywords: History, Photography, Fine Art